Production competitiveness of regional sorghum genotypes against new, enhanced varieties and their morphological traits in Gunung Kidul, Yogyakarta, Indonesia - Muazam, Arif; Daryono, Budi Setiadi; Kristamtini, Kristamtini (Society for Indonesian Biodiversity, 2023)
Sorghum is an important cereal crop after rice, maize, wheat and barley. Sorghum can be a potential local food to supportnational food security and to anticipate the threat of a world food crisis. One effort that can be madeis to optimize the land by using adaptivesorghum varieties planted during the rainy season. Various new superior varieties have been released through the Ministry ofAgriculture, but the germplasm withapotential to be local food has not been utilized optimally. Several studies on sorghum have been carried out from both cultivation and post-harvest aspects, but to continue the research relay and to participate in meeting national food needs,characterization of local varieties needs to be carried out as a first step in plant breeding activities.This study aims to determine the performance of six genotypes of new high-yielding sorghum varieties and localvarieties grown duringthe rainy season in Karangmojo Village, Karangmojo Sub-district, Gunung KidulDistrict, Yogyakarta Province, fromOctober 2022toMarch 2023. The design used was a Randomized Block Complete Design, with 5 repetitions. The resultsshowed the significantly different effect of genotypes on the parameters of plant height, panicle length, panicle width, 1000 seed weight, floweringage, stem diameter, harvesting age, panicle weight per plot, and production per hectare.